The poetic place as origin and horizon: America and Amereida (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
Amereida constitutes a university movement, originated in a poem and a particular historical conjuncture that, together with a confluence of biographical, cultural, artistic and theoretical situations, allowed, among other things, the generation of a body of texts of collective authorship, community-based and personal, deeply imbricated in the vision of the cultural situation of the country and the continent, and an artistic community project that still supports its foundations. A particular work initiated this path: the epic poem Amereida. Made from a common experience and event of a journey through America in 1965, it will become the beginning of this community, university and American movement, as well as, such beginning, gave voice and writing to a series of reflective and theoretical texts about a new situation of the "poetic word" in the experience of an American inhabit: a poetry that must be realized by everyone from the opening of a common place.